FAKTOR DOMINAN ANAK MENJADI ANAK JALANAN DI KELURAHAN AUR KECAMATAN MEDAN MAIMUN - AGUSTIAR MUSLIM (Welfare StatE, 2013)
Many children who are not fulfilled needs, especially those coming from poor, so they work to encourage the economic needs of the family. The phenomenon of street children, especially in urban areas, is a classic problem faced by the government. This study aims to describe the dominant factor of children becoming street children in Kelurahan Aur, Kecamatan Medan Maimun. This research is classified as descriptive study by using the descriptive statistics analysis. The population in this research were 23 children in Kelurahan Aur, with the presentation of data using a single table system. The data collection method was through questionnaires, interviews, and direct observation in the field. The result shows that the dominant factor of children becoming street children in Kelurahan Aur is social environment with peers influence category. This is due to the presence of communal habits of children’s intercommunication in Kelurahan Aur. However, these social factor do not stand alone in influencing children become street children, there are also factors such as omission of the society, initiative of the children, parenting of the family, economics of the family, and opportunities of the employment. Keywords: Street Children, Kelurahan Aur, Social Environment